(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
This paper mainly studies computer automatic measurement of cashmere diameter and area of cashmere fiber scales. It firstly uses Matlab7.0 to do simulation experiments to determine the appropriate image processing program that is suitable for fiber images obtained under optical microscope. The workflow of image processing includes image format conversion, image denoising, image segmentation, binarization, extraction of fiber edge and modificatory process. After image processing, it obtains the necessary binary image needed by the automatic measurement of parameters. The binary image is the basis of diameter and scale-area measurement of cashmere. This paper designs sub-measurement algorithm to achieve the automatic measurement of fiber diameter and pixel-measurement through pixel-by-point scanning to achieve the automatic measurement of area of cashmere fiber scales. It eliminates the error caused by the influence of man-made factors and improves the accuracy of the measurement, which lays the foundation of automatic identification.